(untitled) (ModaPalavra e-periódico, 2017)
This project addresses social inclusion, as a resource to be stimulated by the development of fashion products. Taking into account this market demand research, part of the project, identified aspects of use, accessibility, comfort and perception of parents and therapists with regard to dress, undress and cognitive development in relation to clothing. The audience researched this project were wheelchair children with age range from eight totwelve years, parents and professionals in the health field, such as Physiotherapists, Physical Educator, Occupational Therapist and psychologists, members of institutions CEAEHH -Centro de Atividades Especiais Helena Holanda e FUNAD –Fundação Centro Integrado de Apoio ao Portador de Deficiência, João Pessoa -PB, supporters this project through the sale of infrastructure and public access. The data resulted in the development of a fashion collection with differentiated modeling, versatility of uses combined with an aesthetic framework that prioritized the inclusion of wheelchair-bound child in society through the use of the usual market trends in the children’s segment.